Kajian Teologi Pemujaan Gaņeśa di Pura Ponjok Batu Kecamatan Tejakula Kabupaten Buleleng - Windya, Ida Made; Marselinawati, Putu Sri (Jurnal Penelitian Agama Hindu, 2023)
The existence of the dieties of Gaņeśa and the Nandini ox in one place at Ponjok Batu Temple has caused many perceptions, considering that in Hindu literature it is stated that the ox is the vehicle of Lord Shiva and the rat is the vehicle of Lord Gaņeśa. The purpose of this research is to find out the function and meaning of the theology of worshiping God Gaņeśa at Ponjok Batu Temple. This research includes descriptive qualitative research, the primary data source of this research is the result of interviews with informants. Data collection methods in this study are interviews, library research, and observation. The worship of Ganeśa and the Nandini ox at Ponjok Batu Temple has a theological function, namely the function of Ganeśa as a barrier to obstacles or awighneswara, the function of Ganeśa as the god of war which is proven every ceremony (piodalan) offering arrow dance, the function of worshiping Ganesha and the Nandini ox is a fusion of two sects Ganeśa as a symbol of the Ganapati sect while the Nandini ox as a symbol of the Saiwa sect, and the function of giving knowledge is known in Hindu literature that Ganeśa is the god of wisdom and knowledge. The worship of Lord Ganeśa at Ponjok Batu Temple has a meaning that is felt by the people of Tejakula, namely, the tattwa meaning that worship of Lord Gaņeśa leads to liberation, the meaning of Bhakti Yoga, namely the belief that Hindus worship Ganeśa sincerely reflects one way of liberation, namely bhakti-yoga, and the meaning of family, because at Ponjok Batu Temple not only worships Gaņeśa, but also iwa and the ox Nandini who are one Shiva family.